TunR2, a novel mode-of-action tunicamycin-type antibiotic : Pharmacokinetics in C57BL/6 mouse and Holstein cattle - Colombatti Olivieri, Maria Alejandra; Cassmann, Eric D.; Jackson, Michael A.; Price, Neil P. J.; Bannantine, John P. (Public Library of Science, 2025)
We have investigated the pharmacokinetics of TunR2, a modified tunicamycin-type antibiotic, in mice and cattle. TunR2 has previously been shown to be effective in a mycobacterial disease model using zebrafish, with a minimal activation of the eukaryotic unfolded protein response (upr) and a reduction in the in vivo mycobacterial burden. In this study, we presented statistically relevant pharmacokinetics of native tunicamycin (Tun) and two less toxic modified analogs, TunR2 and TunR1, using a well-defined clonal C57BL/6 mouse (both male and female). Blood samples were collected at multiple time points, and plasma concentrations were quantified using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Pharmacokinetic parameters were calculated using a two-compartment analysis. Our findings indicate that Tun and TunR1 tend to distribute in tissue compared to TunR2, which has a longer half-life than Tun. This translates into longer TunR2 activity time, potentially allowing for less frequent dosing than Tun or TunR1. We subsequently administered the modified TunR2 to Holstein cattle using a three-bolus intravenous regimen. We monitored blood, milk, urine, and feces over 90 days. In dairy cattle, the pharmacokinetics of TunR2 appear to be cumulative, and clear after 10 days. These findings provide critical new insights into the pharmacokinetics of TunR2. We concluded that TunR2 has considerable potential for treating bacterial infections, particularly as an antimicrobial adjuvant with well-established β-lactam antibiotics. Further studies are required to study safety and optimize dosing regimens for effective therapeutic use, as well as in combination with other antibiotics, such as β-lactams.